Incidencia del e-Learning en la evaluación de créditos PYME de la Caja Municipal de Ahorro y Crédito Trujillo – Agencia Tarapoto en el año 2012 - Mori López, Piero Joel (2014)
The present research studies the incident or impact that has the current system of training and on line evaluation (E-Learning) used by the “Caja Trujillo” in the evaluation of credits SME in the Agency - Tarapoto 2012. In order to improve the deficient level of the credit evaluations, which fulfills a fundamental issue because it minimizes the credit risk and assures the good path of the credit, the present work has as aim, improve the level of the credit evaluations SME on the part of the advisers of business, taken charge of the credit grant. The sample of the study was 18 advisers of business location in the credit placement SME of a total of 32 workers of the Agency Tarapoto – 2012, which work in the different cities of the San Martin region. The hypothesis was aimed on “The effective use of the E-Learning helps to improve significantly the credit evaluation SME of the bank company Caja Municipal de Ahorro y Credito de Trujillo – Agency Tarapoto”. The study was a quantitative type and experimental design since there was manipulated the independent variable (system E-Learning) being studies in two periods March – May and June – August. Technologies of bibliographical systematizing were used, review of records, the accomplishment of a questionnaire and statistical analyses, which allowed to obtain information and to sue her, with the intention of confirming the hypothesis, The result of the investigation could happened the hypothesis concluding so the use the effective use of the E-Learning helped to improve significantly the credit evaluation SME of the “Caja Municipal de Ahorro y Credito de Trujillo – Agency Tarapoto”